Kinetic modeling and reaction pathways for thermo-catalytic conversion of carbon dioxide and methane to hydrogen-rich syngas over alpha-alumina supported cobalt catalyst - Alsaffar M.A.; Ayodele B.V.; Ali J.M.; Abdel Ghany M.A.; Mustapa S.I.; Cheng C.K. (Elsevier Ltd, 2023)
Activation energy; Catalysis; Catalyst supports; Cobalt; Deposition; Greenhouse gases; Hydrogen production; Kinetic parameters; Kinetic theory; Methane; Surface reactions; Alpha alumina; Alumina-supported cobalt catalyst; Carbon deposition; Catalytic conversion; CH$-4$; Cobalt-alpha alumina catalyst; Greenhouses gas; Kinetic models; Reaction pathways; Thermo-catalytic conversion; Carbon dioxide